Do Job Seekers Understand the UI Benefit System (And Does It Matter)? - Steffen Altmann; Sofie Cairo; Robert Mahlstedt; Alexander Sebald (Institute of Labor Economics (IZA), 2022)
We study how job seekers' understanding of complex unemployment benefit rules affects their labor market performance. Combining data from a large-scale scale field experiment, detailed administrative records, and a survey of unemployed job seekers, we document three main results. First, job seekers exhibit pronounced knowledge gaps about the prevailing unemployment benefit rules and their personal benefit entitlements. Second, we show that a low-cost information strategy using a personalized online tool increases job seekers' understanding of the rules and their personal benefit situation. Finally, we document heterogeneous labor-market effects of the intervention depending on job seekers' baseline knowledge and beliefs, their personal employment prospects, and the timing of the intervention during the benefit spell.
Keywords: J68; J64; D83; C93; 330; unemployment benefits; field experiments; information frictions; labor market policy; job search